Managing Cattle on Timberlands: Forage Management - Chris Demers; Rob Clausen (EDIS)
This document is SS-FOR-20, one of a series of the School of Forest Resources and Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published: July 2002.